Responsiveness of monetary policy to financial stress in Turkey - Ferhat Camlica (Central Bank Review (CBR), 2016)
The objective of this paper is to investigate whether the Central Bank of Turkey (CBRT) was responsive to financial stress or not during the period 2005m1–2015m10. The study is unique in the sense that CBRT's monetary policy reaction function is augmented with a distinctive financial stress index, i.e. the composite index of systemic stress (CISS). The index pays special attention to the systemic risk component of financial markets by taking into account the cross-correlations between financial market segments. The responsiveness of the CBRT to financial stress is measured by a generic policy interest rate, comprising of the overnight rate, BIST interbank rate and weighted average funding rate. CBRT has publicly announced the change in its policy framework as a response to heightened financial stability concerns after the third quarter of 2010. This study aims to look whether the CBRT's response to financial systemic stress has really changed or not after 2010 by carrying out a subsample regression analysis. The results are further crosschecked with rolling window and interaction dummy regression analysis. The empirical results collected from these econometric exercises indicate that the CBRT's monetary policy was leaning more against financial stress after mid-2010 compared to the previous period.
Keywords: 330; Monetary policy rule; Financial stress; Inflation